MANAGING PREGNANT CARDIAC PATIENTS IN A TERTIARY CARDIAC CARE UNIT IMPROVES FETOMATERNAL OUTCOME - Ansari, Asma; Khalil, Hafsa; Javed, Rehana; Pervaiz, Farrah (Pakistan Armed Forces Medical Journal, 2015)
Objective: To observe the frequency of fetomaternal complications in a cohort of high risk pregnant cardiac patients in a dedicated facility Study Design: Descriptive observational study. Place and Duration of Study: This study was conducted at AFIC/NIHD Rawalpindi from July 2014 to Dec 2014. Methodology: All the patients booked for antenatal and admitted to obstetrics ward AFIC/NIHD for child birth were included. Their cardiac disease and functional status were determined. Maternal cardiac and obstetric complications, fetal complications and maternal mortality rate were recorded. Data was collected and descriptive analysis was done using SPSS. Results: A total of 73 pregnant cardiac patients were studied. Mean age was 28 years SD=4.3 yrs, mean parity was P 2, gestation at delivery was 36.93 SD= 4.8. Eight% patients were booked and 19% were unbooked. The patients were divided by cardiac lesions into 70% rheumatic heart disease, 12.4% congenital heart disease, 9.6% arrhythmias, 6.8% cardiomyopathy and 1.4% pulmonary hypertension. Mode of delivery was 37% LSCS, 52% vaginal delivery, 9.6% instrumental vaginal delivery and 1.4% assisted breech delivery. Maternal complications included cardiac and obstetric complications. Cardiac complications were 8.2% cardiac failure, 4.1% arrhythmia and 1.4% pulmonary embolism. 86.2% had no cardiac complication. Maternal mortality was 2.7%, intrauterine deaths were 5.5%. Conclusion: Closed vicinity of obstetrics ward with operation theatre and twenty four hour availability of cardiologists, cardiac anaesthetists and, dedicated midwifery staff improves the pregnancy outcome in these high risk patients. The fetomaternal outcome is almost comparable to normal obstetric population.